Contribution of the lower extremity joints to mechanical energy in athletics curve sprinting - Heinrich, K.; Alt, T.; Funken, J.; Brueggemann, G. P.; Potthast, W. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purposes of this study were to identify differences of the three-dimensional joint kinetics between linear and curve sprinting and to quantify the asymmetrical loading of both legs during curve sprinting. Six male sprinters performed three linear and curve sprints. The energies of the ankle, knee and hip joint were determined during the ground contact phase with the aid of an adjusted multibody human model. The ankle joint was the largest energy absorber and generator in the sagittal plane while the hip joint was the largest energy absorber and generator in the frontal and transversal plane. Asymmetric functions of the inside and outside leg were determined during curve sprinting. The hip joint of the inside leg might be highly loaded in sprinting on a bend track.